Biological Materials: The Next Frontier for Cell-Free Synthetic Biology - Kelwick, Richard J. R.; Webb, Alexander J.; Freemont, Paul S. (Frontiers in Bioengineering and Biotechnology, 2020)
Advancements in cell-free synthetic biology are enabling innovations in sustainable biomanufacturing, that may ultimately shift the global manufacturing paradigm towards localised and ecologically harmonised production processes. Cell-free synthetic biology strategies have been developed for the bioproduction of fine chemicals, biofuels and biological materials. Cell-free workflows typically utilise combinations of purified enzymes, cell extracts for biotransformation or cell-free protein synthesis reactions, to assemble and characterise biosynthetic pathways. Importantly, cell-free reactions can combine the advantages of chemical engineering with metabolic engineering, through the direct addition of co-factors, substrates and chemicals - including those that are cytotoxic. Cell-free synthetic biology is also amenable to automatable design cycles through which an array of biological materials and their underpinning biosynthetic pathways can be tested and optimised in parallel. Whilst challenges still remain, recent convergences between the materials sciences and these advancements in cell-free synthetic biology enable new frontiers for materials research.